Evaluación del actual sistema de gas licuado de petróleo y su incidencia en el laboratorio de petroquímica de la universidad de las fuerzas armadas – espe – extensión Latacunga durante el año 2016. propuesta de diseño de un sistema centralizado de gas licuado de petróleo. - Ruiz Flores, Luis Eduardo (2018)
The present investigation has been directed to achieve a constructive solution of the stationary installation of LPG, for the Petrochemical Laboratory of the Armed Forces University - ESPE – Latacunga Extension, which will be used for teaching and research purposes, and it is intended to replace the previous installation from the operational problems that has been presented. An analysis is made of the characteristics of the original installation, its deficiencies and the requirements that the new installation must meet. The material and dimensions of the pipes were determined, as well as the different valves and accessories to be used. The hydraulic balance of the network was obtained with the help of the Pipe Flow Expert v.5.12 software, achieving a design solution that satisfies the requirements of mass flow, pressure and speeds throughout the network and at the delivery points of the service in each laboratory equipped with Bunsen burners. From the obtained values, the Computational Fluid Dynamics (CFD) simulation was performed with CAE tools to check the hydraulic performance of the propane gas subnet belonging to the L1-Engineering Laboratory, for representing the most severe conditions of the driving while being located at the end of the service network.